Trends in Complications Among Patients Undergoing Aortic Valve Replacement in the United States - James E. Harvey; Samir R. Kapadia; David J. Cohen; Ankur Kalra; William Irish; Candace Gunnarsson; Michael Ryan; Soumya G. Chikermane; Christin Thompson; Rishi Puri (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background The treatment of severe aortic stenosis has evolved considerably since the introduction of transcatheter aortic valve replacement (TAVR), yet trends in complications for patients undergoing TAVR or surgical aortic valve replacement (SAVR) at a national level have yet to be evaluated. Methods and Results We performed a retrospective cohort study using Medicare data to evaluate temporal trends in complications among beneficiaries, aged ≥65 years, treated with elective isolated transfemoral TAVR or SAVR between 2012 and 2019. The study end point was the occurrence of a major complication (composite outcome) during index and up to 30 days after. Multivariable logistic regression was used to assess odds of complications for TAVR and SAVR, individually over time, and for TAVR versus SAVR, over time. The cohort included 211 212 patients (mean±SD age, 78.6±7.3 years; 45.0% women). Complication rates during index following elective isolated aortic valve replacement decreased from 49% in 2012 to 22% in 2019. These reductions were more pronounced for TAVR (41% to >19%, Δ=22%) than SAVR (51% to >47%, Δ=4%). After risk adjustment, the risk of any complication with TAVR was 47% (P<0.0001) lower compared with SAVR in 2012, and 78% (P<0.0001) lower in 2019. TAVR was independently associated with reduced odds of complications each year compared with 2012, with the magnitude of benefit increasing over time (2013 versus 2012: odds ratio [OR], 0.89 [95% CI, 0.81–0.97]; 2019 versus 2012: OR, 0.35 [95% CI, 0.33–0.38]). These findings are consistent for complications up to 30 days from index. Conclusions Between 2012 and 2019, the risk of complications after aortic valve replacement among Medicare beneficiaries decreased significantly, with larger absolute and relative changes among patients treated with TAVR than SAVR.